2020
DOI: 10.1111/ajt.15584
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept-based immunosuppression: A calcineurin inhibitor-sparing regimen in heart transplant recipients

Abstract: | INTRODUC TI ONCalcineurin inhibitors (CNI) are the backbone of immunosuppression in solid organ transplantation, but long-term exposure is often associated with nephrotoxicity. 1 Belatacept (BTC) (Nulojix ® ) is a highaffinity CTLA4Ig indicated for the prophylaxis of graft rejection in adults receiving a renal transplant in combination with mycophenolic acid (MPA) and corticosteroids. 2,3 The BENEFIT study demonstrated that BTC-based regimens were associated with a similar incidence of acute rejection but im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
(31 reference statements)
2
22
2
Order By: Relevance
“…The CNI avoidance strategy of early conversion to mammalian target of rapamycin (mTOR) inhibitor-based therapy has demonstrated efficacy in preserving renal function, 25 but is suboptimal and limited by the adverse outcomes characteristic of the mTOR inhibitor class (eg, pneumonitis, wound complications, metabolic toxicities). Successful posttransplant conversion to belatacept in nonrenal solid organ transplantation has been previously reported, 26 , 27 but very few instances have been observed in liver transplant recipients. The largest experience in liver transplantation consisted of the successful use of belatacept as a temporary bridge to renal recovery in 7 recipients with hepatitis C, 28 but the duration of belatacept treatment was short, ranging from 19 to 89 d and all patients were converted back to CNIs.…”
Section: Discussionmentioning
confidence: 99%
“…The CNI avoidance strategy of early conversion to mammalian target of rapamycin (mTOR) inhibitor-based therapy has demonstrated efficacy in preserving renal function, 25 but is suboptimal and limited by the adverse outcomes characteristic of the mTOR inhibitor class (eg, pneumonitis, wound complications, metabolic toxicities). Successful posttransplant conversion to belatacept in nonrenal solid organ transplantation has been previously reported, 26 , 27 but very few instances have been observed in liver transplant recipients. The largest experience in liver transplantation consisted of the successful use of belatacept as a temporary bridge to renal recovery in 7 recipients with hepatitis C, 28 but the duration of belatacept treatment was short, ranging from 19 to 89 d and all patients were converted back to CNIs.…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4Ig costimulatory blockade is currently widely used in clinical organ transplantation (45)(46)(47)(48). Recent long-term clinical trials in kidney transplant patients have shown improved graft function, better cardiovascular/metabolic risk profile and similar patient and graft survival when compared to CNIs.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter retrospective non-comparative cohort study of 40 heart transplant recipients in France switched from CNI to belatacept, mainly due to impaired renal function on CNI, Launay et al ( 34 ) found that belatacept was associated with a high rate discontinuation and adverse effects. At the end of follow-up, 4/40 (10%) of patients had died (2 of fatal rejection, 1 of invasive infection, 1 of non-compliance).…”
Section: Non-randomized Studiesmentioning
confidence: 99%